Transnational habitus: Educational, bilingual and biliteracy practices of Chinese sojourner families in the U.S. (September 2019) - Chao, Xia; Ma, Xiufang
Grounded in the perspectives of language socialization and transnational habitus, this one-year ethnographic case study explores two middle-class Chinese sojourner families' educational, bilingual and biliterate practices after their arrival in the U.S. It addresses the process that their middle childhood children experienced, from the excitement of the new English-speaking environment to linguistic and social isolation, to their adaptation to the environment and, finally, to transnational uplift. The families' transnational practices throughout the four phases are shaped by their economic, educational and sociocultural dispositions that link together their country of origin and the U.S. They tend to cross national borders in language, literacy and education as well as to circulate glocalized English–Chinese biliteracy. This study reveals the disjunction between the families' "imagined world" of the U.S. and the reality of a language barrier and ideological conflicts underpinned in an English-only society. The families' transnational migration is an educational practice with access to their children's "imagined world". This study suggests that ESL learning should be considered as a socialization practice, which is tied to and structured by transnational fields in today's globalized world.